IMPROVING TEACHERS 'COMPETENCY IN IMPLEMENTING BASIC LEARNING BY GIVING TASKS THROUGH THE WHATSSAPP SOCIAL MEDIA APPLICATION AT VOCATIONAL SCHOOL OF ISLAM INNAYAH UJUNG BATU 2020/2021 - Eka Fitri (JURNAL PENDIDIKAN ROKANIA, 2020)
The problem raised in the study was the low competence of teachers in implementing online and offline learning that was in accordance with the standard process during the Covid-19 outbreak. Meanwhile, one of the teacher's duties is to carry out meaningful learning in order to achieve maximum learning objectives. The purpose of this study is to improve competence in implementing online and offline learning through guidance with the consultation method for teachers at the Islamic Vocational School Innayah Ujung Batu in 2021. From the results of the research conducted by researchers, 37 teachers have an understanding of online learning in the Fairly Good category, 25 people. The teacher has understanding of online learning in the Good category, and 31 teachers have understanding of online learning in the Very Good category. Based on the results of this study, it is found that the competence of implementing online and offline learning can be improved by the method of giving assignments through the Whatssapp application with teachers of Inayah Islamic Vocational School, Ujung Batu